Basal accretion, a major mechanism for mountain building in Taiwan revealed in rock thermal history. (February 2018) - Chen, Chih-Tung; Chan, Yu-Chang; Lo, Ching-Hua; Malavieille, Jacques; Lu, Chia-Yu; Tang, Jui-Ting; Lee, Yuan-Hsi
Graphical abstract: Highlights: An integrated time-temperature history is revealed for the pro-wedge of Taiwan. The crucial role of basal accretion is credited based on age and thermal data. Basal accretion led to mountain root growth prior to late rapid exhumation. Abstract: Deep tectonic processes are key integral components in the evolution of mountain belts, while observations of their temporal development are generally obscured by thermal resetting, retrograde alteration and structural overprinting. Here we recorded an integrated rock time-temperature history for the first time in the pro-wedge part of the active Taiwan arc-continent collision starting from sedimentation through cleavage-forming state to its final exhumation. The integrated thermal and age results from the Raman Spectroscopy of Carbonaceous Material (RSCM) method, zircon U-Pb laser ablation dating, and in-situ 40 Ar/ 39 Ar laser microprobe dating suggest that the basal accretion process was crucial to the development of the Taiwanese orogenic wedge. The basal accretion process commenced early in the mountain building history (∼6 Ma) and gradually migrated to greater depths, as constrained by persistent plate convergence and cleavage formation under nearly isothermal state at similar depths until ∼ 2.5 Ma recorded in the early-accreted units. Such development essentially contributed to mountain root growth by the increased depth of the wedge detachment and the downward wedge thickening during the incipient to full collision stages in the Taiwan mountain belt.